Geothermal Energy - Ismail, Basel I. (IntechOpen, 2022)
Geothermal energy for electricity generation is an appealing solution to reducing greenhouse gas emissions produced by fossil fuels. As such, this book presents a comprehensive overview of the research related to and the potential applications of geothermal energy. Chapters cover such topics as power technology using low-temperature geothermal energy resources, current world status of geothermal resource utilization, low-temperature district heating systems, and much more.